Research of the Isogeometric Analysis of Gear Frictionless Contact - Xu Huan; Yang Guolai; Zheng Jianguo; Ge Jianli (Jixie chuandong)
The isogeometric analysis method（IGA）is expanded to frictionless contact problem.The contact constraint is introduced into the system potential energy function by using the penalty function method.The modeling and contact analysis of the involute gear are carried out by using the type of the multi-patch NURBS curved surface piece stitch.The result from IGA model is compared with that calculated by finite element model,and which shows that proposed method has advantages including high precision of calculation and smooth stress field,and an effective method for solving contact problem is provided.